Implementation of the C4.5 Algorithm in Predicting the Interest of Prospective Students in Choosing Higher Education - Triraharjo, Bambang; Ayu Minarni, Prilian; Baskoro (Information System; Universitas Buana Perjuangan Karawang, 2025)
Data governance involves setting internal standards for how data is collected, stored, processed and deleted. In the context of the oil industry, data governance can intervene at the level of oil exploration and production to manipulate data in particular. In our contribution, we explain how Fuzzy c - means based machine learning can be used for oil data governance. This deep artificial intelligence concept, which we will use in addition to fuzzy logic, by applying Fuzzy c - means for good training can enable the decision-maker a better governance policy.